Feed Preference, Adaptation, and Role of The Eurasian Tree Sparrows (Passer montanus L.) in Urban and Rural Environments - Pratiwi, Ika; Priyambodo, Swastiko; Hernowo, Jarwadi Budi (CROPSAVER, 2022)
The Eurasian tree sparrow (Passer montanus L.) known as both pest and predators; in the urban area, it is considered a pest because of its droppings, feathers, and nests around the house. Meanwhile, in rural areas, it is considered both pests and predators because their diets are small insects and small grains like a grain in the rice field. This study aimed to determine the daily consumption rate of sparrows on grain; their preferred food; identify the adaptability; and the role of sparrows in urban and rural areas. Feeding ability test using the no-choice baiting method. Food preference test using the choice baiting method. The adaptability and role of sparrow data are obtained through location determination and direct observation in the field. The results show that the consumption rate of individual sparrow is ten percent of body weight. The most preferred food for sparrow is yellow mealworm, followed by millet, cricket, foxtail millet, rice grain, and corn. The Eurasian tree sparrow is not considered a pest on rice fields. The presence of the sparrow in urban areas is less than in rural areas. Both in urban and rural areas, more sparrows were seen or found in the morning than in the afternoon. Sparrows can adapt well in rural and urban areas because the environment provides open area and house building. In urban areas, sparrow is considered urban pests; meanwhile in rural areas they potentially considered a pest on barley and millet, and predators on small insects.